'the whole window just shatters into a million pieces and it doesn't make any sound': an examination of 'affordance' and situational cues for theft from a motor vehicle. Issue 4 (October 2018) - Quinn, Anthony; Grove, Louise
Abstract Much offending, particularly acts of acquisitive crime, is influenced by whether there is a discernible opportunity to take advantage of. The success of this can be determined by the presence or absence of certain characteristics in the immediate environment and how they are interpreted to facilitate gain by an offender. This study explores some of these techniques or 'affordances' that have been adopted by individuals when seeking to commit Theft from a motor vehicle offences. This insight is gleaned through qualitative one-to-one interviews with participants who have received criminal convictions for this crime type. There is an evaluation of how offender awareness of affordances could lead to the vulnerability of certain contexts as subsequently, ideas of countermeasures against these offending opportunities are offered.